2009
DOI: 10.1073/pnas.0900190106
|View full text |Cite
|
Sign up to set email alerts
|

Essential global role of CDC14 in DNA synthesis revealed by chromosome underreplication unrecognized by checkpoints in cdc14 mutants

Abstract: The CDC14 family of multifunctional evolutionarily conserved phosphatases includes major regulators of mitosis in eukaryotes and of DNA damage response in humans. The CDC14 function is also crucial for accurate chromosome segregation, which is exemplified by its absolute requirement in yeast for the anaphase segregation of nucleolar organizers; however the nature of this essential pathway is not understood. Upon investigation of the rDNA nondisjunction phenomenon, it was found that cdc14 mutants fail to comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 65 publications
2
51
0
Order By: Relevance
“…Cdc14 is a cell cycle regulatory protein that localises to nucleoli throughout most of the cell cycle. These yeast mutants exhibit heterochromatin under-replication but this does not trigger cell cycle checkpoints and does not alter replication-associated gene expression immediately; rather, this defect is manifested during the next cell cycle (Dulev et al, 2009). Essentially the same situation was observed in our system, including the changes in replication-associated transcripts at the 2-cell stage.…”
Section: Discussionsupporting
confidence: 57%
“…Cdc14 is a cell cycle regulatory protein that localises to nucleoli throughout most of the cell cycle. These yeast mutants exhibit heterochromatin under-replication but this does not trigger cell cycle checkpoints and does not alter replication-associated gene expression immediately; rather, this defect is manifested during the next cell cycle (Dulev et al, 2009). Essentially the same situation was observed in our system, including the changes in replication-associated transcripts at the 2-cell stage.…”
Section: Discussionsupporting
confidence: 57%
“…By contrast, a previous study has discounted Cdc14p as the physiological phosphatase that dephosphorylates initiation proteins to promote pre-RC formation and DNA replication (Noton and Diffley, 2000). A recent study has reported genome-wide under-replication in cdc14-1 cells, which was attributed to dosage insufficiency of some replication proteins; however, the possible function of Cdc14p in promoting replication licensing by dephosphorylating pre-RC components was not addressed (Dulev et al, 2009). Therefore, the essential role of Cdc14p in replication licensing remains controversial.…”
Section: Introductionmentioning
confidence: 82%
“…Misshapen kinetochores can lead to merotelic microtubule attachments, lagging anaphase chromosomes, and ultimately gains and losses of whole chromosomes in daughter cells ( 45 ). Alternatively, centromere fusions or recombination with other chromosomes ( 7,8 ) may lead to gains or losses of whole chromosome arms, and these are the most common segmental chromosome changes in human cancer ( 46 ). Finally, lagging chromosomes created by these mechanisms are more likely to become incorporated into micronuclei and undergo chromothripsis in subsequent cell cycles ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unrepaired errors can be passed on to daughter cells and contribute to cancer ( 1 ). In general, damaged DNA signals the cell cycle to arrest, and Replication stress can lead to fork stalling and chromosomal aberrations ( 7 ). It can create short gaps in sequence, or unresolved replication intermediates ( 3 , 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%